Mindful practice with medical interpreters - Roman, Gretchen; Yousefi-Nooraie, Reza; Vermilion, Paul; Cupertino, Anapaula; Barnett, Steven; Epstein, Ronald (Frontiers in Psychology, 2023)
Introduction Medical interpreters experience emotional burdens from the complex demands at work. Because communication access is a social determinant of health, protecting and promoting the health of medical interpreters is critical for ensuring equitable access to care for language-minority patients. The purpose of this study was to pilot a condensed 8-h program based on Mindful Practice® in Medicine addressing the contributors to distress and psychosocial stressors faced by medical sign and spoken language interpreters. Methods Using a single-arm embedded QUAN(qual) mixed-methods pilot study design, weekly in-person 1-h sessions for 8 weeks involved formal and informal contemplative practice, didactic delivery of the week's theme (mindfulness, noticing, teamwork, suffering, professionalism, uncertainty, compassion, and resilience), and mindful inquiry exercises (narrative medicine, appreciative interviews, and insight dialog). Quantitative well-being outcomes (mean±SEM) were gathered via survey at pre-, post-, and 1-month post-intervention time points, compared with available norms, and evaluated for differences within subjects. Voluntary feedback about the workshop series was solicited post-intervention via a free text survey item and individual exit interviews. A thematic framework was established by way of qualitative description. Results Seventeen medical interpreters (46.2 ± 3.1 years old; 16 women/1 man; 8 White/9 Hispanic or Latino) participated. Overall scores for teamwork (p ≤ 0.027), coping (p ≤ 0.006), and resilience (p ≤ 0.045) increased from pre- to post-intervention and pre- to 1-month post-intervention. Non-judging as a mindfulness component increased from pre- to post-intervention (p = 0.014). Compassion satisfaction (p = 0.021) and burnout (p = 0.030) as components of professional quality of life demonstrated slightly delayed effects, improving from pre- to 1-month post-intervention. Themes such as workshop schedule, group size, group composition, interactivity, topics to be added or removed, and culture are related to the overarching topic areas of intervention logistics and content. Integration of the findings accentuated the positive impact of the intervention. Discussion The results of this research demonstrate that mindful practice can serve as an effective resource for medical interpreters when coping with work-related stressors. Future iterations of the mindful practice intervention will further aspire to address linguistic and cultural diversity in the study population for broader representation and subsequent generalization.